Antidumping as Safeguard Policy - Finger, J. Michael (World Bank, Washington, DC, 2014)
Antidumping is by far the most prevalent instrument applied by countries to impose new import restrictions. In the 1980s antidumping was used mainly by a handful of industrial countries. More recently developing countries have used it increasingly often. Since the World Trade Organization (WTO) Agreements went into effect in 1995, developing countries have initiated 559 antidumping cases, developed countries 463 (through June 2000). Per dollar of imports ten developing countries have initiated at least five times as many antidumping cases as the United States. Even so, the WTO community continues to take up antidumping as if it were a specialized instrument. In reality, present WTO rules allow it to be applied in any instance of politically troubling imports. The authors argue that, as a "pressure valve" to help maintain an open trade policy, antidumping has serious weaknesses: Its technical strictures do not distinguish between instances that advance rather than harm the national economic interest. And its politics of branding foreigners as unfair strengthens rather than mutes pressures against liberalization.